Проективний метод у психологічній роботі з учасниками АТО - Мушкевич, Мирослава Іванівна; Mushkevych, Myroslava I. (Східноєвропейський національний університет імені Лесі Українки, 2015)
Стаття презентує ті проективні методики, які застосовуються в психологічній науці для вивчення особистісних характеристик людини, які не вербалізуються, приховуються, завуальовуються чи заперечуються. Виявлено, що не потребуючи великих затрат часу та відзначаючись простотою процедури проведення, проективний метод є достатньо інформативним та дозволяє виявити не лише свідомі установки, а й неусвідомлені, про які досліджувані не хочуть розповідати. Обґрунтуванно та емпірично досліджено особистісні характеристики учасників АТО проективним методом.

The article presents the projective techniques that are used in psychological science for the study of personal characteristics of people which are not verbalized, are hidden or denied. It was found that projective method is quite informative and reveals not only the conscious attitude, but also unconscious, which does not want or can not be disscussed. It is grounded and empirically there were investigated such personal characteristics of ATO participants: negative emotional feelings of depression, sadness, passiveness, dissatisfaction, disillusionment, despair; low self-esteem, low level of socialization, low adaptation to difficult situations; high level of anxiety, emotional discom fort, stress, concerns, fears, anguish; passive response in all situations; psychological characteristics that could negatively impact on ove rcoming problems; low level of aggression, more control over their own behavior; introversion, non-communicativeness, isolation, passivity, indeci sion, care, commitment to accuracy, pedantry, social disadaptation; feelings of discomfort, anxiety, insecurity, a sense of powerlessness, lack of aspiration, painful perception of life difficulties; disfunctional emotional family background, such asanxiety about the family situation, low levels of interpersonal violence, distrust to each other, everyone lives by itself and others; fragmentation of the family, each family member is living according to their interests, without taking into account the views of other members of the family, the family spends very little time together; dissatisfaction with a family situation, when everybody needs emotional warmth, wants to spend more time with the family, wants changes for the better family situation.
Projective techniques in psychological work with ATO participants
Keywords: проективний метод; учасники АТО; особистісні характеристики; міжособистісна взаємодія; психологічна діагностика; психологічна допомога; projective techniques; ATO participants; personal characteristics; interpersonal communication; psychological assessment; psychological assistance